(3MRH Gdfhhjs - (3jMji Hf TQa Hf eQj Hf MSf GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjG, eMjj GdOjf , (B676 (3g` s ((3CMeO GdhGUdj GdShjaj GdeGdcjs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg hSde HSe Gddg Gddg CcHQ Gddg CcHQ bhd Ydi faSj hYdi Ojfj hYdi Cgdj hYdi ChdGOj hYdi eGdj hYdi CUMGHj hYdi COjGfge hYdi CehGdges
(3BNQgG (B:s
(3dc Gddge Yf faSj eG CWjb heG dG CWjb dG WGbI deNdhb eY bOQI GdNGdb MSHj Gddg hfYe Gdhcjd hUdi Gddg Ydi SjOfG eMeOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 8 / 149s
(3eYLe GdeDdajf(B: 4 / 98s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs